1996
DOI: 10.1073/pnas.93.10.4608
|View full text |Cite
|
Sign up to set email alerts
|

Nest predation by cowbirds and its consequences for passerine demography.

Abstract: Brood parasitism by brown-headed cowbirds (Molothrus ater) reduces reproductive success in many passerines that nest in fragmented habitats and ecological edges, where nest predation is also common. We tested the hypothesis that parasitism and predation are often linked because cowbirds depredate nests discovered late in the host's nesting cycle to enhance future opportunities for parasitism. Over a 20-year study period, brood parasitism by cowbirds was a prerequisite to observing marked inter-and intraannual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 16 publications
7
116
0
Order By: Relevance
“…They showed that such host populations can only be maintained in a metapopulation framework with immigration from other, less parasitized areas. But continued exploitation of hosts can have important conservation implications in rare and localized hosts (Rothstein & Robinson 1994;Arcese et al 1996;Trine et al 1998). The effect of parasitism by Brown-headed Cowbirds, for example, is not restricted to reducing the reproductive success of hosts, but can skew host offspring sex-ratios (Zanette et al 2005) and affect host population growth rate significantly (Smith et al 2002).…”
Section: Coevolutionary Arms Races: Ongoing Struggle or Stalemate?mentioning
confidence: 99%
“…They showed that such host populations can only be maintained in a metapopulation framework with immigration from other, less parasitized areas. But continued exploitation of hosts can have important conservation implications in rare and localized hosts (Rothstein & Robinson 1994;Arcese et al 1996;Trine et al 1998). The effect of parasitism by Brown-headed Cowbirds, for example, is not restricted to reducing the reproductive success of hosts, but can skew host offspring sex-ratios (Zanette et al 2005) and affect host population growth rate significantly (Smith et al 2002).…”
Section: Coevolutionary Arms Races: Ongoing Struggle or Stalemate?mentioning
confidence: 99%
“…Perhaps as a result, the Brown-headed Cowbird lacks some adaptations possessed by other brood parasites (Mermoz and Ornelas, 2004) including mimicry of host eggs (Rothstein and Robinson, 1998; but see Peer et al 2002), or evidence of specialized nestling adaptations such as directly killing nestmates (Lichtenstein and Sealy, 1998;Peer et al, 2013). Among the adaptations possessed by cowbird are that females have a larger hippocampus to remember where host nests are located (Sherry et al, 2003); laying eggs rapidly and before sunrise to avoid detection by hosts (Scott, 1991;Sealy et al, 1995; see also Peer and Sealy, 1999b); thick eggshells presumably to withstand puncture-ejection by hosts (Picman, 1989); greater pore diameter in their eggshells for increased embryonic respiration and shorter incubation periods (Jaeckle et al, 2012; see also Briskie and Sealy, 1990); removal of host eggs by females in conjunction with parasitism to enhance incubation efficiency (Peer and Bollinger, 1997; and for nutrition (Sealy, 1992); egg puncture and killing nestlings to force hosts to renest providing additional chances for parasitism (Arcese et al, 1996;Elliott, 1999;Hoover and Robinson, 2007;Dubina and Peer, 2013); and possibly forcing hosts to accept parasitism through mafia enforcement tactics (Hoover and Robinson, 2007).…”
mentioning
confidence: 99%
“…Shiny cowbirds do not use punctures to reset yellowwinged blackbirds nesting attempts as was suggested for brown-headed cowbirds (Arcese et al 1996;Peer & Sealy 1999). The number of punctured eggs was no higher in long-incubated, non-parasitized nests than the number of punctured eggs at newly incubated parasitized nests, as would be expected if cowbirds were attempting to force their hosts to renest.…”
Section: Discussionmentioning
confidence: 99%